Pineapple leaf fiber (PALF) waste as an alternative fiber in making concrete. Issue 1 (1st February 2022) - Karolina, Rahmi; Tandika, William; Hasibuan, Azhari; Agung Putra, M.; Fahreza, Devi
Abstract: Indonesia is the 9th largest pineapple producer in the world with a production of 1.39 million tons per year. this makes the pineapple leaf fiber (PALF) waste available abundantly in Indonesia. Palf waste has not been widely used in Indonesia. palf is usually used as fabric for textiles or yarn to be used as clothes and as handicrafts. palf has excellent mechanical properties and is environmentally friendly. in this study palf is used as a material for construction. Adding fiber to the concrete mixture is one way to minimize cracks in the concrete. This study aims to increase the compressive strength, tensile strength of concrete and utilize palf potential as construction material. This study compares the compressive strength and tensile strength of normal concrete against compressive strength and tensile strength of concrete with the addition of pineapple fiber with variations of 0%, 0.5 %, 1%, 1.5% to the weight of cement. The specimen used was a cylinder with a diameter of 15cm and a height of 30cm. The test is carried out on specimens with the age of 28 days. Experimental results show that inclusion of Palf improves the split tensile strength and compressive strenghth of concrete.